2005
DOI: 10.1021/nl051027p
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Excitonic Radiative Decay in CdSe Quantum Dots:  The Role of Surface Hole Traps

Abstract: Using atomistic, semiempirical pseudopotential calculations, we show that if one assumes the simplest form of a surface state in a CdSe nanocrystal--an unpassivated surface anion site--one can explain theoretically several puzzling aspects regarding the observed temperature dependence of the radiative decay of excitons. In particular, our calculations show that the presence of surface states leads to a mixing of the dark and bright exciton states, resulting in a decrease of 3 orders of magnitude of the dark-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
200
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(217 citation statements)
references
References 27 publications
14
200
1
2
Order By: Relevance
“…3 are not accord with the Stern-Volmer equation. This implies that there may be static quenching, dynamic quenching or even multiple quenching pathways [14]. The PL quenching of QDs comes from two possible processes: static quenching and dynamic quenching [15].…”
Section: Resultsmentioning
confidence: 99%
“…3 are not accord with the Stern-Volmer equation. This implies that there may be static quenching, dynamic quenching or even multiple quenching pathways [14]. The PL quenching of QDs comes from two possible processes: static quenching and dynamic quenching [15].…”
Section: Resultsmentioning
confidence: 99%
“…In our pseudopotential calculations, emission from the lowestenergy exciton has finite oscillator strength (and thus finite lifetime), because of the atomistic character of the band-edge single-particle wave functions and the coupling with higher-energy excitonic configurations in the many-body CI Hamiltonian. Recent atomistic calculations [15] have shown that, in the presence of surface states, the lowest-energy exciton acquires significant oscillator strength, due to the mixing of dark and bright excitonic states.…”
Section: B Many-body Effects On the Transition Energies And Radiativmentioning
confidence: 99%
“…[18][19][20][21][22][23] Further studies focussed on the oxidation of QD, [24] or photo-induced charge transfer, [11] and also on the influence of experimental conditions, such as temperature or pH. [7,25,26] Herein we present a systematic study on the interaction of nucleotides and amino acids with QD, which occasionally leads to a significant quenching of fluorescence intensity. For our studies we used two different commercially available core shell QD, QD655 and QD705, with a ZnS shell and a CdSe and CdTe core respectively.…”
Section: Introductionmentioning
confidence: 99%